2017
DOI: 10.1111/imb.12309
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in acetylcholinesterase 1 associated with chlorpyrifos resistance in the brown planthopper, Nilaparvata lugens Stål

Abstract: Insecticide resistance frequently results from target-site insensitivity, such as point mutations in acetylcholinesterases (AChEs) for resistance to organophosphates and carbamates. From a field-originated population of Nilaparvata lugens, a major rice pest, a resistant population (R9) was obtained by nine-generation continuous selection with chlorpyrifos. From the same field population, a relatively susceptible population (S9) was also constructed through rearing without any insecticides. Compared to the susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…In the present study, the 2.09‐fold SR of TPP in a 271.78‐fold resistant strain indicates that other mechanisms might also be involved in the resistance to chlorpyrifos in the BPH (Table 1). This conclusion was supported by the target‐site insensitivity data from recombinant AchE proteins, and three mutations (G119S, F331C and I332L) in AchE1 were identified to be associated with chlorpyrifos resistance in the BPH (Zhang et al ., 2017). However, the role of CarE‐mediated metabolism on chlorpyrifos resistance is a somewhat open question as the synergist concentrations may not be optimized, the synergistic effects of TPP could be undervalued in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the 2.09‐fold SR of TPP in a 271.78‐fold resistant strain indicates that other mechanisms might also be involved in the resistance to chlorpyrifos in the BPH (Table 1). This conclusion was supported by the target‐site insensitivity data from recombinant AchE proteins, and three mutations (G119S, F331C and I332L) in AchE1 were identified to be associated with chlorpyrifos resistance in the BPH (Zhang et al ., 2017). However, the role of CarE‐mediated metabolism on chlorpyrifos resistance is a somewhat open question as the synergist concentrations may not be optimized, the synergistic effects of TPP could be undervalued in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Both target insensitivity and metabolic detoxification mechanisms underlying chlorpyrifos resistance have been identified in the BPH (Lu et al ., 2017b; Zhang et al ., 2017). Kinetics analysis of recombinant protein and biochemical inhibition assays demonstrated that resistance to chlorpyrifos results from the mutations in the target site, the AChE, a serine hydrolase that terminates nerve impulse transmission by hydrolyzing the neurotransmitter acetylcholine at cholinergic synapses (Zhang et al ., 2017). Another mechanism of resistance to chlorpyrifos described in the BPH is the enhanced production of carboxylesterases (CarEs) (Lu et al ., 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…В ряде работ резистентность к ФОС (в том числе к хлорпирифосу) и к карбаматам, связывают с мутациями АХЭ, что делает невозможным связывание инсектицида и АХ. Показано это на примере высокорезистентных популяций вредителей сельского хозяйства -цикадках, тлях, белокрылках [32,33]. У рыжего таракана устойчивая АХЭ встречается достаточно редко -частоты резистентных аллелей генов нечувствительной к ФОС и карбаматам АХЭ составляют 0,03-0,08 [14].…”
Section: Discussionunclassified
“…With the generation of resistance and cross resistance on the harmful pests in agriculture, and the banning use of pesticides with high toxicity and poor environmental compatibility . The agricultural pests often brought about actual losses in productivity of crops all over the world annually .…”
Section: Introductionmentioning
confidence: 99%